Maize and semiotic emergence in a contemporary Maya Tale: Tec Tun's, U tsikbalo'ob XNuk Nal [Tales of Old Mother Corn]. Issue 1 (1st January 2019) - Pigott, Charles Maurice
ABSTRACT: This article discusses a contemporary Maya story about the relationship between humanity and maize in the Yucatan Peninsula: José Manuel Tec Tun's, U tsikbalo'ob XNuk Nal / Los cuentos de la Abuela Mazorca [Tales of Old Mother Corn]. It argues that the story depicts a process that the recent biological field of biosemiotics terms "semiotic emergence" (Hoffmeyer): the evolution of higher stages of complexity through the interaction between previous levels. This argument is advanced through the lens of the Maya concept of óol or "existential growth" which displays close similarities with the concept of "final cause" as defined by the philosopher, Charles Sanders Peirce, a major influence in biosemiotics. Through textual analysis of the Maya and Spanish versions, the article shows how Tec Tun's story depicts maize and humanity as mutually oriented towards nurturing each other in a relationship of "structural coupling" (Maturana and Varela): the co-constitution of habitat and inhabitant. This interaction results in the emergence of symbolism, a complex stage of semiotic emergence that can, at least partially, account for the central role of maize in human consciousness for Maya cosmology.